2016
DOI: 10.1371/journal.pbio.1002475
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of High Cellulolytic Activity in Symbiotic Streptomyces through Selection of Expanded Gene Content and Coordinated Gene Expression

Abstract: The evolution of cellulose degradation was a defining event in the history of life. Without efficient decomposition and recycling, dead plant biomass would quickly accumulate and become inaccessible to terrestrial food webs and the global carbon cycle. On land, the primary drivers of plant biomass deconstruction are fungi and bacteria in the soil or associated with herbivorous eukaryotes. While the ecological importance of plant-decomposing microbes is well established, little is known about the distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 77 publications
2
66
0
Order By: Relevance
“…These include spatial and temporal heterogeneity in substrate availability and community structure (88), seasonal differences in transcriptional response (89), expression of isoenzymes and/or uptake transporters with different K m / V max tradeoffs (2), gene-gene interactions (90), and interactions between substrate quality, quantity, and microbial physiology (24). Furthermore, metagenomics is liable to access the genomes of both active and inactive, living and dead cells (91).…”
Section: Discussionmentioning
confidence: 99%
“…These include spatial and temporal heterogeneity in substrate availability and community structure (88), seasonal differences in transcriptional response (89), expression of isoenzymes and/or uptake transporters with different K m / V max tradeoffs (2), gene-gene interactions (90), and interactions between substrate quality, quantity, and microbial physiology (24). Furthermore, metagenomics is liable to access the genomes of both active and inactive, living and dead cells (91).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a variety of Streptomyces strains isolated from soil have been shown to grow on cellulose (16, 120, 144), hemicellulose (45, 61), and potentially even lignin (34, 163) (Figure 2 b ). However, the majority of strains tested cannot grow on crystalline cellulose or hemicellulose, suggesting that most Streptomyces species in the soil only use the breakdown products of plant cell wall polymers (18). Other genera of Actinobacteria have also been implicated in plant biomass degradation in the soil, including Cellulomonas , Nocardia , and Micromonospora , again on the basis of their high prevalence in soil and the ability of some isolates to grow on plant biomass-derived substrates (57, 90, 163).…”
Section: Ecology Of Actinobacteriamentioning
confidence: 99%
“…Clustering observed in phylogenetic analysis with other insect-associated Actinobacteria, however, may suggest a more permanent association between Actinobacteria and the termite gut. Book et al (2016) identified a number of Streptomyces clades dominated by host-associated strains. Genetic similarity of Actinobacteria isolated in this study with bacteria from these host-associated lineages may be supportive of a more stable association.…”
Section: Discussionmentioning
confidence: 99%